A short review on investigation and suppression of tool chatter in turning operation. (2022) - Katiyar, Shivani; Jaiswal, Muskan; Pratap Narain, Ratneshwar; Singh, Sarthak; Shrivastava, Yogesh
Abstract: Tool chatter is a big stumbling block in machining operations which includes; turning, milling, and drilling. During machining processes, self-excited vibrations are caused due to the inhomogeneous material properties this results in the creation of a wavy profile on the surface of the material. A lot of work has been reported in this domain. However, it is very essential to summarize the reported works together, to make it suitable for the readers to understand and extrapolate the future requirements. In the present work, different chatter monitoring techniques have been explored and summarized to highlight the features of each and to identify the best suitable technique among them.